Penerapan Model Pembelajaran Team Based Project Untuk Meningkatkan Hasil Belajar Tematik Siswa Kelas IV SDN 104252 Sei Tuan T.A 2022/2023 - Mahyaruddin Zaky, Irfan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Based on observations in class IV SDN 104252 Sei Tuan learning outcomes in thematic learning, especially theme 1 in understanding the Main and Supporting material, Sound Energy, and specifically in Social Religion material. This study aims to improve student learning outcomes by applying the Team-Based Project learning model to the subject matter of Basic and Supporting Infrastructure, Sound Energy. This type of research is